1976
DOI: 10.1128/iai.13.2.438-447.1976
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus population dynamics in the respiratory tract of experimentally infected mice

Abstract: Virus population dynamics in the lungs, trachea, and nasopharynx of Swiss-ICR mice were studied after respiratory challenge with mouse-adapted preparations of strain A2/Aichi/2/68 influenza virus. Markedly higher doses of virus were required to produce infection with nasopharyngeal challenge than with bronchoalveolar challenge. In all of the infections, the highest virus concentrations were observed in the lungs. Peak concentrations in the trachea were lower than in the lungs but higher than in the nasopharynx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 8 publications
1
34
0
2
Order By: Relevance
“…Our data showed that viral loads are maintained at a high level between 2 d and 7 d pi (Figure 1). Sustained viral loads have been observed in several studies [6,10,21,24,38,46,51]. In some data sets, the peak appears more pronounced and is often followed by the plateau phase or a second, lower peak [1,4,6,10,17,21,24].…”
Section: Discussionmentioning
confidence: 94%
“…Our data showed that viral loads are maintained at a high level between 2 d and 7 d pi (Figure 1). Sustained viral loads have been observed in several studies [6,10,21,24,38,46,51]. In some data sets, the peak appears more pronounced and is often followed by the plateau phase or a second, lower peak [1,4,6,10,17,21,24].…”
Section: Discussionmentioning
confidence: 94%
“…While the dynamics of influenza A virus have been investigated in various studies, the dynamics of influenza B virus, 103 which is also an important public health threat, have not been analyzed using kinetic models. The models developed thus far also generally do not incorporate multiple compartments, such as the lung, trachea, and nasopharynx, 61 that may have interesting dynamical differences. Integrating the extracellular events (e.g., virus production and infected cell death) with the intracellular kinetics (e.g., RNA replication and virus assembly) 23 or the transmission between hosts 104,105 may give insight into the various aspects of influenza pathogenicity including why some strains cause more inflammation or are more easily transmitted.…”
Section: Discussionmentioning
confidence: 99%
“…The flrst is that even freshly harvested virus preparations contain an excess of non-infectious virions, and these may persist in the mouse because permissive replication does not take place in the spleen [15] or footpad [this paper]. Even after the initial rapid replication of influenza virus in the lungs, the virus titre levels off [5,18], and this may reflect an accumulation of non-infectious virions. Thus, the mouse would be sensitized to produce both classes of DTH effector cells when infectious influenza virus preparations were injected.…”
Section: Discussionmentioning
confidence: 99%